Circumareolar Versus Circumvertical Mastopexy with Augmentation - Basim A. Awan, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The main aim of augmentation mastopexy is to obtain harmonic relation between breast volumes, shape and scar. There are several variations of the modified breast lift, including circumareolar and circumvertical techniques, each of which has its own unique characteristics and approaches. The aim of this retrospective study was to evaluate and compare the uses of circumareolar (n = 55, 27.20%) versus circumvertical (n = 147, 72.80%) augmentation-mastopexy in 202 women over a 10 years period. Results showed that 28 patients (50.90%) with circumareolar augmentation-mastopexy need revised surgery due to undesired breast shape (n = 24, 43.60%), stretched areola (n = 17, 30.90%) and bad scar (n =9, 16.40%); while 32 patients (22.40%) with circumvertical augmentation-mastopexy need revised surgery due to secondary ptosis (n = 29, 19.70%), large areola (n =3, 2.00%) and unpleasant vertical scar (n = 13, 8.80%). The present study concluded that circumareolar augmentation-mastopexy procedure showed less satisfactory results with undesirable breast and areola shape and bad scars, while circumvertical augmentation-mastopexy gives better results for the areola and breast shape with less potential revision.